Pilote Mensuel. (Dargaud, 1978)
Contiene: Historietas de los sirvientes Autores: Don Martín; Coucho y Pailler; Lacroix; Jaquelin; Freud; Christin y Lesveur; Loro M. Franc y Lesueur; Hippolyte; Marol; Resis Franc.